An Analysis on Background, Archaeology and the Indus Civilization under Vedic Time: Uncovering the Spiritual and Psychological Roots of Ancient Vedic Society (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The ancient civilisations can give some brilliant pieces of information to understanding the spiritual and psychological roots of human society and culture. In this mission, Vedic society and culture of ancient India can be a rich wellspring of understanding, since it was manufactured, guided and formed by spiritual diviners and masterminds who had a profound knowledge into the spiritual and psychological elements of life. A profound comprehension of the society, culture and religion of the early Vedic society can illuminate the internal causes of human civilization. Be that as it may, scientific and discerning personality alone and its target standpoint can't do this adequately.